CONTROL AND RECOGNITION OF ANIONIC LIGANDS IN MYOGLOBIN - CUTRUZZOLA', Francesca; TRAVAGLINI ALLOCATELLI, Carlo; BRUNORI, Maurizio; Paolo Ascenzi; Martino Bolognesi; Stephen G. Sligar (FEBS Letters, 1991)
Equilibrium and kinetic experiments on site-directed mutants of a synthetic sperm whale myoglobin (Mb) gene have been performed. Results on the reactivity on both ferric and ferrous wild type and mutants Mb's are presented. Analysis of ligand binding to His(E7)Val and His(E7)Val-Thr(E10)Arg mutants compared to wild-type sperm whale, horse and Aplysia limacina Mb's, shows that the introduction of an arginyl residue at the topological position E10 greatly enhances the stability of the various Mb:heme ligand adducts. Alternative mechanisms of ligand stabilization may therefore be operative in Mb's lacking the distal histidine.